Docking molecular e interações não-covalentes de compostos originais derivados de 2-aril-oxazolinas em enzimas de Candida spp - Silva, Rui Filipe Nogueira da (Universidade Federal de São Carlos, 2019)
Candidiasis is a mycosis caused by fungi of the genus Candida spp. It affects up to 50% of the world's population and may progress to candidaemia, leading to death in up to a half of patients. Commercial drugs used in its treatment belong to three families, exist for about half a century and target only two cellular components of the fungus, the cell membrane and the cell wall. In the last decade, reports of new Candida species resistant to one or more of these traditional drugs make urgent the need to find new drugs, specially targeting new fungal metabolic pathways. In order to face this problem, the research group of Prof. Helio A. Stefani from USP's Faculty of Pharmaceutical Sciences synthesized 26 compounds derived from 2-aryl-oxazoline, carrying out biological studies on five species of fungi of the genus Candida, obtaining the MIC50 values. In this work, the use of in silico methods envisioned the identification of a molecular target for the 2-aryl oxazoline compounds in Candida spp. and the characterization of the interactions that may be responsible for the MIC50 values. Therefore, molecular docking experiments were carried out with the 26 modeled ligands on the enzymes dihydrofolate reductase from Candida albicans and lanosterol 14-α-demethylase from Candida glabrata. The monitoring and the characterization of the main non-covalent interactions of the 26 ligands with the proteins, specifically the Candida albicans dihydrofolate reductase, pointed an important interaction of the substituent halides with the enzyme’s glutamic acid 32 residue, and the interaction of the ligands with the tyrosine 21-leucine 29 protein loop, namely CH...π interactions with methionine 25 residue. The reported interactions supported the correlation of the in silico experiments with the results of the biological assays. Analysis of the docking results and the non-covalent protein-ligand interactions allowed the branding of dihydrofolate reductase as a potential target of oxazoline-derived compounds in Candida albicans.
Molecular docking and non-covalent interactions of original 2-aryl-oxazoline derived compounds in Candida spp
Keywords: Candidíase; Aril-oxazolinas; Docking molecular; Interações não-covalentes; GOLD; NCIPLOT; Diidrofolato redutase; Candidiasis; Aryl-oxazolines; Molecular docking; Non-covalent interactions; Dihydrofolate reductase; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA::MODELAGEM DE SISTEMAS BIOLOGICOS; CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS; CIENCIAS BIOLOGICAS::BIOFISICA; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS::PROTEINAS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::MEDICAMENTOS